Comparing the remineralization potential of undemineralized dentin powder versus chicken eggshell powder on artificially induced initial enamel carious lesions: an in-vitro investigation - Mai Badreldin Helal; Mai Samy Sheta; Wafaa Yahia Alghonemy (BMC, 2024)
Abstract Background White spot lesions are a widespread undesirable effect, especially prevalent during fixed orthodontic treatments. The study compared the in vitro enamel remineralization potential of undemineralized dentin matrix (UDD) versus chicken eggshell powder (CESP) for artificially induced enamel lesions. Methods 100 caries-free and sound maxillary premolars were randomly divided into four groups each contain 25 teeth: Group I (Baseline): No treatment was done to the enamel surface. Group II (Negative control ): The enamel surface of the teeth underwent demineralization using demineralizing solution to create artificial carious lesions then kept in artificial saliva. Group III (CESP treated): After demineralizing the tooth surface, the teeth have been suspended in the CESP remineralizing solution. Group IV (UDD treated): After enamel demineralization, the teeth were suspended in UDD remineralizing solution. The remineralization potential was assessed by Vickers microhardness testing, scanning electron microscopic examination (SEM), and energy dispersive X-ray (EDX). Results The current study demonstrated an increase in the mean microhardness of CESP and UDD-treated groups; however, It was nearer to the baseline level in the UDD group. SEM imaging revealed greater enamel remineralization in the UDD group compared to the remaining groups. The UDD group disclosed complete coverage for the prismatic enamel compared to the CESP group, which revealed a partially remineralized enamel surface. Interestingly, the Ca/P ratio increased significantly in the CESP group compared to the negative control group. In contrast, a higher significant increase in the mean Ca/P ratios was recorded in the UDD group compared to the test groups. Conclusion biomimetic UDD and CESP powder should be utilized to treat enamel early carious lesions. However, UDD demonstrated the most significant remineralization potential.